Analisis Pengaruh Integrasi Etika dan Pengembangan Kecerdasan Terhadap perilaku Etis Calon Akuntan - Yazid, Afifatun Nikmah Rizqiyah; Safitri, Novika Rahayu (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study aims to provide empirical evidence regarding the contribution of ethics to accounting education, ethics integration, and intelligence development to the ethical attitudes of prospective accountants. The population of this study consisted of accounting students who had completed financial accounting courses. This study used a stratified random sampling technique, where 100 respondents were selected from various classes to ensure sample representativeness. The results of the analysis showed that all questions asked to respondents had been proven valid. The results of the hypothesis test of this study indicate that the contribution of ethics to financial accounting education has a positive and significant influence on the ethical attitudes of prospective accountants. In addition, ethics integration also has a positive and significant influence on the ethical attitudes of accounting students, and intelligence development has a positive impact on their ethical attitudes. The questionnaire test showed that variables that include ethical content in financial accounting courses, ethics integration, and intelligence development can explain 44.3% of the variability in the ethical attitudes of accounting students, 47.4% in intelligence development, and the remaining 8.3% can be explained by other variables. Overall, the results of this study provide evidence that the integration of ethics in accounting education and intelligence development play an important role in shaping the ethical attitudes of prospective accountants.